Aristotle And Al-Ghazali: A Comparative Study On Their Educational Theories And Contributions - Rahimah, Embong; Abdul Hakim, Abdullah; Wan Mazwati, Wan Yusoff; Mohamed, Ibrahim (2017)
This paper aims to analyze Aristotle’s educational theory with that of al-Ghazali and to identify the significance and influence of their theories to Western and Muslim civilizations and worldwide. Aristotle and Imam al-Ghazali were two immortals of history who put their seal on European and Muslim philosophical scholarship through succeeding generations. Aristotle (384 –322 B.C) Aristotle was the founder of Western philosophical realism while al-Ghazali (1058- 1111 A..D.) was the reformer of Muslim civilization. He advocated that Revelation is essential to recognize the reality and that is granted specifically to Messenger of God by The Almighty. In term of methodology, this study examines some primary and secondary sources of related literature. It used comparative document analysis. Upon analyzation of their philosophy, Aristotle defined “happiness” as the virtuous life and gave to education a major role in developing arête, or virtue, that generalized and encompassing excellence or perfection. On the other hand, al–Ghazali advocated that one who combines moral and intellectual greatness is the devout sage and his reward will be absolute bliss. He highlighted the objective of education is utility. Aristotle recognized that education directly related to both the healthy individual and the harmoniously integrated society. Meanwhile, Al-Ghazali had suggested a golden principle that subjects should be taught in their order of utility and importance. In summary, both of these intelligentsia gave a lot of influences and contributions in the field of education. Indeed, Aristotle and al-Ghazali had successfully shaped the whole intellectual tradition of the West and laid the philosophical foundations of Western Culture and Islamic scholasticism.